ANALISIS EFEKTIVITAS PERATURAN KEMENTERIAN KEUANGAN NOMOR 169/PMK.010/2015 (PMK-169) (STUDI EMPIRIS ATAS PERUSAHAAN PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2016) - Arfah Habib Saragih (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2018)
State revenue from the taxation sector remains dominating over revenue from other sources. This revenue will be constantly increased in the future. In so doing, the Government has issued the Minister of Finance Regulation Number 169/PMK.010/2015 (PMK-169). This regulation sets the debt-to-equity ratio allowable for firms in general at four to one (4:1) and has been effective from tax year 2016. This is necessary to avoid thin capitalization practice that can lower state revenue from the taxation sector as it opens a tax avoidance opportunity for firms through interest-based debt. This research was intended to analyse the effectiveness of PMK-169 for firms listed on the Bursa Efek Indonesia over 2015 (before) and 2016 (after). By employing paired sample t-test analysis technique on 316 observations of 158 firms, it was proven that there was a significant difference in the debt-to-equity ratio as well as tax avoidance before and after the enactment of the regulation. The implication of this finding is that PMK-169 as a debt control regulation is considered effective to implement.